Study of the Utility of NWP Forecast Guidance and Simple Ocean Modeling as a Tool for Planning During Reactive Situations - Jones, Robert D. (2007)
The utility of using a numerical weather prediction (NWP) forecast model as an input to a simple ocean model for planning during reactive situations is studied. An oceanographic experiment called the Maud Rise Nonlinear Equation of State Study (MaudNESS) was conducted from June to September of 2005 over the Maud Rise in the eastern Weddell Sea. Archived Antarctic Mesoscale Prediction System (AMPS) Polar MM5 forecast fields from MaudNESS were compared to observed conditions during MaudNESS. AMPS was found to have problems with cloud and moisture parameters, but represented the overall synoptic situation. AMPS forecast and observed forcing fields (as well as increased values for both) were input into a simple one dimensional ocean model at three locations in the Maud Rise area of differing stability. The ocean model was found to have good utility as a planning tool for short term reactive situations where a high degree of accuracy is not needed.